Tinjauan Literatur tentang Pendekatan Pembelajaran Bulutangkis Berbasis Game dalam Pendidikan Jasmani - Sahabuddin (PT. PENERBIT TIGA MUTIARA, 2025)
This study presents the results of a systematic literature review highlighting the effectiveness of game-based badminton learning approaches as a relevant instructional strategy in physical education. A review of eight selected articles indicates that the integration of game-oriented activities can enhance students’ fundamental technical skills, tactical understanding, and enthusiasm throughout the learning process. An in-depth analysis of the findings reveals that learning models that position students at the center of activity are able to facilitate more meaningful learning experiences through game situations that closely resemble real on-court conditions. Furthermore, the interaction patterns created through game activities contribute to the development of psychomotor skills and increase students’ readiness to engage confidently in competitive scenarios. Evaluation of various forms of implementation suggests that game-based learning innovations, whether through structured models or application-based media, hold significant potential to improve the quality of badminton instruction. Nevertheless, this review also identifies several challenges, including limited long-term studies, research concentration at specific educational levels, and insufficient exploration of affective and cognitive variables. These findings emphasize the need for further research with broader coverage to gain a deeper understanding of how game-based approaches can be implemented sustainably and deliver optimal benefits for students’ competency development across diverse physical education contexts in Indonesia.